Effects of walking speed and prosthetic knee control type on external mechanical work in transfemoral prosthesis users. (March 2022) - Pinhey, Shay R.; Murata, Hiroto; Hisano, Genki; Ichimura, Daisuke; Hobara, Hiroaki; Major, Matthew J.
Abstract: During human locomotion, each limb performs step-to-step work on the body center of mass to maintain forward walking. This energy exchange relies on physiological mechanisms which are altered or impaired in transfemoral prosthesis users (TFPUs). Exploring step-to-step energy exchange modifications displayed by TFPUs at greater walking speeds may provide insight into their means for improving gait efficiency. The primary aim of this study was to characterize the effects of walking speed on mechanical work in unilateral TFPUs. The secondary aim assessed the effect of prosthetic knee (microprocessor, mechanical passive) on limb collision work. Twenty-five TFPUs walked with their customary prosthesis on a split-belt instrumented treadmill at eight speeds (0.55–1.53 m/s range), and collision, midstance, and push-off work were calculated for each limb. TFPUs displayed a significant (p < 0.001) bilateral increase in collision work with increased walking speed, but midstance and push-off work increased only for the sound limb and remained nearly constant for the prosthetic limb. TFPUs displayed significantly (p < 0.001) less push-off work generated by the prosthetic limb across all speeds. A microprocessor knee was associated with reduced sound limb collision work across speeds with the peak (negative) power being significantly greater for mechanical knees (p = 0.032). Results suggest that TFPU gait inefficiency may be related to a near complete loss of energy transfer on the prosthetic limb, relying on the sound limb to drive energy changes. Such reliance emphasizes need for attention to the long-term effects on sound limb health and possible benefit of microprocessor knees to offset that impact.